Pelaksanaan Sistem Digital di Disnaker Kota Pekanbaru - Ajeng Putri Antia; Chica Nabila Octariani; Tengku Alfira Masyitah; Elly Niel Waty (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze the implementation of digital systems in the Pekanbaru City Manpower Office. This research uses a qualitative approach which aims to produce descriptive data. Data collection techniques applied include interviews, observation and documentation. Based on research findings, it was found that there is potential for implementing SIMANJA (Inter-Employment System) in the Pekanbaru City Manpower Office as an effort to increase the efficiency and effectiveness of employment services. Although the specifics regarding SIMANJA in the Pekanbaru City Manpower Office have not been found, an analysis based on general practices of inter-employment systems shows information about SIMANJA's great potential in simplifying the job search process, increasing the accessibility of job information, and increasing the transparency of the scanning process. This article also identifies several challenges to SIMANJA implementation, such as data integration, data security, promotion and outreach, and digital community literacy. It is recommended that the Pekanbaru City Manpower Office make efforts to overcome this challenge, so that SIMANJA can be an effective solution in improving Pekanbaru city power services.